The Politics of Organizing Refugee Camps - Maximilian Schellmann (Copenhagen Business School (CBS), 2018)
This thesis reflects on refugee camps as spaces of organizing and investigates the politics, which are enacted and produced through such. Refugee camps have largely been neglected as sides and sites of organizing within recent studies of organization. This thesis therefore seeks to situate sites of organizing such as refugee camps - which literally are placed at the margins, both of space as well as of organizational discourses - at the centre.
hdl:10398/9691
Keywords: 650